2001
DOI: 10.1002/1097-0215(20010601)92:5<622::aid-ijc1256>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of human immunodeficiency virus infection and cancer in adults and children residing in Kampala, Uganda

Abstract: Uganda offers a unique setting in which to study the effect of human immunodeficiency virus-1 (HIV-1) on cancer. HIV-1 is prevalent there, and cancers which are known to be HIV-associated, such as Kaposi's sarcoma and Burkitt's lymphoma, are endemic. Adults residing in Kampala, Uganda, presenting with cancer in city hospitals were interviewed and had an HIV test. Of the 302 adults recruited, 190 had cancers with a potentially infectious aetiology (cases). The remaining 112 adults with tumours not known to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 0 publications
4
30
1
Order By: Relevance
“…3 HIV infection itself is a major risk factor leading to a 10 fold increase in conjunctival tumours in Africa. 5,7,19 Ocular manifestations occur in 50% to 75% of the patients with HIV infection sometime during the course of the disease. The most common ophthalmic manifestations associated with HIV infection in India have been reported to be HIV retinopathy, cytomegalovirus retinitis (20%), and opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…3 HIV infection itself is a major risk factor leading to a 10 fold increase in conjunctival tumours in Africa. 5,7,19 Ocular manifestations occur in 50% to 75% of the patients with HIV infection sometime during the course of the disease. The most common ophthalmic manifestations associated with HIV infection in India have been reported to be HIV retinopathy, cytomegalovirus retinitis (20%), and opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Between 1994 and 1998, we recruited adults aged 15 years or older with a new diagnosis of cancer from the wards and outpatient clinics of the main hospitals in Kampala, Uganda (Ziegler et al, 1997Newton et al, 2001Newton et al, , 2002Newton et al, , 2003. After informed consent and counselling, patients were interviewed and tested for infection with human immunodeficiency virus (HIV)-1 using the Cambridge Bioscience Recombigen ELISA (Cambridge, Massachusetts, USA) on sera or the GACELISA method (Murex, Dartford, UK) on saliva.…”
Section: Methodsmentioning
confidence: 99%
“…In a case series of 13 patients from Uganda with squamous cell carcinoma of the penis, all tumour samples contained HPV-DNA, although the specific subtype was unclear (Tornesello et al, 1992). As part of a larger study of cancer in Uganda, we investigated the prevalence of antibodies against in the sera of patients with a range of different tumours (Ziegler et al, 1997Newton et al, 2001Newton et al, , 2002Newton et al, , 2003. Results in relation to conjunctival squamous cell carcinoma have been presented elsewhere, but no clear association with antibodies against HPV-16, -18 or -45 was identified (Newton et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The possible influence of HIV infectionaffecting 1 000 000 people in Uganda in 2004 [23]-cannot be definitely assessed in our collective because of the lack of serologic information. It is of note, however, that several studies showed that the 3-fold increase of BL recorded in Central Africa during the last decades is independent of the HIV epidemic, most if not all patients being negative for the virus [15,23,24]. Moreover, in general, the prevalence of HIV-related lymphomas is much lower in sub-Saharan Africa than in the west (ie, 20 versus 8000-9000 per 100 000 persons per year), infections being the most common cause of death [23].…”
Section: Burkitt's Lymphomamentioning
confidence: 99%